تأثير عوامل الوسط الخارجي على أداء منظومات تشحين المحركات البحرية - معروف أحمد; حسين صلاح يوسف (Tishreen University, 2019)
تؤثر عوامل الوسط الخارجي بشكلٍ كبيرٍ على فعالية أداء محطات القدرة البحرية. وإنّ معرفة مقدار هذا التأثير تُساعد على تحسين المواصفات الاستثمارية والاقتصادية لهذه المحطات. وفي هذا البحث تمت معالجة هذه المسألة باستخدام طريقة النمذجة الرياضية. ولهذا الغرض تم إعداد نموذج رياضي يمثل أداء محطات القدرة البحرية المستخدمة على السفن أثناء إبحارها في منطقة شرق المتوسط، وتمت كتابة البرنامج باستخدام لغة البرمجة Delphi وبرامج Excel، MathCAD. وللتأكد من دقة نتائج هذا النموذج تم إجراء مجموعة من التجارب العملية على المحطات المستخدمة على السفن السورية. واستناداً إلى هذه الدراسة تم إعداد طريقة لاختيار وتعليل أنظمة العمل الملائمة لاستخدام محطات القدرة عند حدوث تغيرات في بارامترات الوسط الخارجي، وتم إعداد بعض التوصيات والإرشادات المتعلقة بزيادة فعالية استخدام محطات القدرة الرئيسة المستخدمة لدفع السفن. External medium parameters have a major effect on the efficiency of marine power plants performance. Comprehension of the amount of these effect helps to improve the economical and exploitational characteristics of this plants. In this research, this problem had been treated using mathematical modeling method. To achieve that purpose a mathematical model designed representing the performance of marine power plants during navigation in eastern region of Mediterranean. The program had been done by Delphi program, Excel and MathCAD. To confirm the accuracy of results of this mathematical model some experiments had been performed upon Syrian ships plants. According to this study a method of selection and explanation of the suitable working systems for using power plant when external medium parameters changes had been performed. Some related suggestions and recommendations are provided to augment the efficiency of using main power plants that can be used to push ships.